Proposal of steel structure form 6th to 12th Story and above works - BUCG-ABC Joint Venture (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC joint venture for proposal of steel structure form 6th to 12th Story and above works of Brac University new campus project.